2019
DOI: 10.1017/s0954579418001190
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary, Randomized-Controlled Trial of Mindfulness and Game-Based Executive Function Trainings to Promote Self-Regulation in Internationally-Adopted Children

Abstract: Although many children adopted internationally show remarkable recovery once placed in families, as a group they continue to exhibit persisting developmental deficits and delays in self-regulation. The current study uses a stratified, randomized, controlled trial to evaluate the effects of mindfulness-based and executive function trainings (EFTs) on internationally adopted (IA) children's self-regulation, including effortful/inhibitory control, attention, delay of gratification, and emotion-regulation. IA chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…Mindfulness training preserved sustained attention on the SART in the mindfulness group relative to the coding group. This finding aligns with prior behavioral studies reporting enhanced cognitive control after mindfulness training in children (Britton et al, 2014; Felver et al, 2017; Flook et al, 2010; Lawler et al, 2019; Leonard et al, 2013; Quach et al, 2016; Salmoirago‐Blotcher et al, 2019; Schonert‐Reichl et al, 2015;Semple et al, 2010; Sidhu, 2012) and adults (Cásedas et al, 2019; Moore & Malinowski, 2009). These RCTs demonstrated improved attentional ability measured by task performance or parent/teacher‐reported questionnaires in typically developing children and adolescents (Felver et al, 2017; Schonert‐Reichl et al, 2015), in children with ADHD (Sidhu, 2012) or reading difficulties (Semple et al, 2010; Sidhu, 2012), and in incarcerated adolescents (Leonard et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mindfulness training preserved sustained attention on the SART in the mindfulness group relative to the coding group. This finding aligns with prior behavioral studies reporting enhanced cognitive control after mindfulness training in children (Britton et al, 2014; Felver et al, 2017; Flook et al, 2010; Lawler et al, 2019; Leonard et al, 2013; Quach et al, 2016; Salmoirago‐Blotcher et al, 2019; Schonert‐Reichl et al, 2015;Semple et al, 2010; Sidhu, 2012) and adults (Cásedas et al, 2019; Moore & Malinowski, 2009). These RCTs demonstrated improved attentional ability measured by task performance or parent/teacher‐reported questionnaires in typically developing children and adolescents (Felver et al, 2017; Schonert‐Reichl et al, 2015), in children with ADHD (Sidhu, 2012) or reading difficulties (Semple et al, 2010; Sidhu, 2012), and in incarcerated adolescents (Leonard et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…A meta‐analysis of RCTs employing mindfulness‐based interventions in adults found a moderate but significant improvement of cognitive control, specifically in attention and memory (Cásedas et al, 2019). For children and adolescents, 8 out of 10 RCTs reported that mindfulness training improved cognitive control and attentional abilities (with an additional trend in a ninth study) (Britton et al, 2014; Felver, Tipsord, Morris, Racer, & Dishion, 2017; Flook et al, 2010; Lawler, Esposito, Doyle, & Gunnar, 2019; Leonard et al, 2013; Quach, Jastrowski Mano, & Alexander, 2016; Salmoirago‐Blotcher et al, 2019; Schonert‐Reichl et al, 2015; Semple, Lee, Rosa, & Miller, 2010; Sidhu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, mindfulness training improved delayed gratification in a sample of internationally adopted children when compared with executive function training (active comparator) and control groups (Lawler, Esposito, Doyle, & Gunnar, 2019). Additionally, 10 weeks of mindfulness training in incarcerated male adolescents revealed gains in global well-being, self-awareness, and self-regulation (Himelstein, Hastings, Shapiro, & Heery, 2012), while a day-long retreat following the 10-week program reinforced these gains and led to future practice in the adolescents (Barnert, Himelstein, Herbert, Garcia-Romeu, & Chamberlain, 2014).…”
Section: Mindfulness-based Approachesmentioning
confidence: 99%
“…Mindfulness has been positively associated with several dimensions of self-regulation (e.g., Bowlin & Baer, 2012; Chambers et al., 2008; Fetterman et al., 2010; Heeren et al., 2009; Howell & Buro, 2011; Short et al., 2015; for a review, see Chiesa et al., 2011), including emotion regulation (e.g., Hill & Updegraff, 2012; Luberto et al., 2014; MacDonald & Baxter, 2017) and delay of gratification (e.g., Flook et al., 2015; Howell & Buro, 2011; Lawler et al., 2019) and negatively associated with impulsivity (Fetterman et al., 2010). Zelazo and Lyons (2012) describe mindfulness as a set of skills that builds the “top-down” reflective components of self-regulatory control, including greater attention and cognitive flexibility, while simultaneously reducing “bottom-up” distractions, such as impulsivity and rumination (p. 156).…”
mentioning
confidence: 99%